Dari Konversi ke Resistensi: Strategi Kebertahanan Agama Lokal dalam Pusaran Pluralitas Terbatas - Apriliyani Harahap; Zaenuddin Zaenuddin (Tamaddun, 2020)
This article discusses the construction of defining religion in Indonesia which cannot be separated from the influence of the world religions paradigm. Indonesia is one of the countries that has implemented a religious management policy based on recognition, through Law no. 1/PNPS 1965 concerning the Prevention of Religious Abuse and/or Blasphemy. This research article focuses on examining how the patterns and strategies adopted by the adherents of local religions in Indonesia can exist in the middle of the vortex of recognition of official religions by the state. With the library research method analyzed using a content analysis approach, this article finds that the patterns and strategies used by adherents of local religions to maintain their existence are conversion or conversion, religious syncretism, and resistance, namely refuses to be affiliated with world religions. The various patterns and strategies that have emerged are the response of local religions to various state policies that co-opt their rights, especially civil rights in services and fulfillment of their needs, including civil registration, access to education, health facilities and facilities, to the registration of marriage. Artikel ini membahas tentang konstruksi pendefinisian agama di Indonesia yang tidak lepas dari pengaruh paradigma agama dunia. Indonesia merupakan salah satu negara yang menerapkan kebijakan pengelolaan agama berdasarkan pengakuan, melalui UU No. 1/PNPS Tahun 1965 Tentang Pencegahan Penyalahgunaan dan/atau Penodaan Agama. Riset artikel ini fokus untuk mengkaji bagaimana pola dan strategi yang diterapkan oleh para penganut agama Lokal di Indonesia agar dapat eksis di tengah pusaran pengakuan agama-agama resmi oleh negara. Dengan metode studi kepustakaan (library research) yang dianalisis menggunakan pendekatan analisis isi (content analysis), artikel ini menemukan bahwa pola dan strategi yang digunakan oleh penganut agama lokal dalam mempertahankan eksistensinya adalah dengan melakukan konversi atau pindah agama, sinkretisme agama, dan resistensi, yakni menolak untuk diafiliasikan dengan agama dunia. Ragam pola dan strategi yang mengemuka ini sebagai respon agama lokal terhadap berbagai kebijakan negara yang mengkooptasi hak-hak mereka, terutama hak-hak sipil dalam pelayanan dan pemenuhan kebutuhannya, baik pencatatan sipil, akses pendidikan, sarana dan fasilitas kesehatan, hingga pencatatan perkawinan.